Magnetic field dependent magnetization of a conducting plasticized poly(aniline) film - Djurado, D.; Pron, A.; Travers, J-P; Duque, J. G. S.; Pagliuso, P. G.; Rettori, C.; Chinaglia, D. L. [UNESP]; Walmsley, L. [UNESP] (Iop Publishing Ltd, 2008)
We report magnetic data of free standing films of poly( aniline) (PANI) protonated with a plasticizing di-ester of succinic acid. The data have been obtained using the electron spin resonance (ESR) technique at two different frequencies, X-band (9.4 GHz) and Q-band ( 34 GHz), on one hand, and by magnetization measurements in broad ranges of temperatures and magnetic fields on the other hand. All the data can be explained assuming a transition as a function of temperature from delocalized magnetic moments in the valence band to localized positive polarons in several antiferromagnetically correlated bands. By increasing the magnetic field, the magnetic properties are affected in several ways. An intra-band admixture of states occurs; it contributes to increase the spins' localization and finally promotes an antiferromagnetic-metamagnetic transition.